Skin‐Like Oxide Thin‐Film Transistors for Transparent Displays. (4th July 2016) - Lee, Han Eol; Kim, Seungjun; Ko, Jongbeom; Yeom, Hye‐In; Byun, Chun‐Won; Lee, Seung Hyun; Joe, Daniel J.; Im, Tae‐Hong; Park, Sang‐Hee Ko; Lee, Keon Jae
Abstract : Flexible transparent display is a promising candidate to visually communicate with each other in the future Internet of Things era. The flexible oxide thin‐film transistors (TFTs) have attracted attention as a component for transparent display by its high performance and high transparency. The critical issue of flexible oxide TFTs for practical display applications, however, is the realization on transparent and flexible substrate without any damage and characteristic degradation. Here, the ultrathin, flexible, and transparent oxide TFTs for skin‐like displays are demonstrated on an ultrathin flexible substrate using an inorganic‐based laser liftoff process. In this way, skin‐like ultrathin oxide TFTs are conformally attached onto various fabrics and human skin surface without any structural damage. Ultrathin flexible transparent oxide TFTs show high optical transparency of 83% and mobility of 40 cm 2 V −1 s −1 . The skin‐like oxide TFTs show reliable performance under the electrical/optical stress tests and mechanical bending tests due to advanced device materials and systematic mechanical designs. Moreover, skin‐like oxide logic inverter circuits composed of n ‐channel metal oxide semiconductor TFTs on ultrathin, transparent polyethylene terephthalate film have been realized. Abstract : Ultrathin, flexible, and transparent oxide thin‐film transistors for skin‐like displays are transferred to an ultrathin flexible substrate using an inorganic based laser liftoff process. The transferred transistor arrays with high mobility of ≈40 cm 2 V −1 s −1 adhere to both fabric and human skin and operate stably without significant degradation of their characteristics. Finally, skin‐like oxide logic inverters are successfully manipulated to verify the dynamic responses on an ultrathin plastic substrate.